Cyclooxygenase‐2 over‐expression inhibits liver apoptosis induced by hyperglycemia1. Issue 3 (22nd January 2013) - Francés, Daniel E.A.; Ingaramo, Paola I.; Mayoral, Rafael; Través, Paqui; Casado, Marta; Valverde, Ángela M.; Martín‐Sanz, Paloma; Carnovale, Cristina E.
Abstract Increased expression of COX‐2 has been linked to inflammation and carcinogenesis. Constitutive expression of COX‐2 protects hepatocytes from several pro‐apoptotic stimuli. Increased hepatic apoptosis has been observed in experimental models of diabetes. Our present aim was to analyze the role of COX‐2 as a regulator of apoptosis in diabetic mouse liver. Mice of C57BL/6 strain wild type (Wt) and transgenic in COX‐2 (hCOX‐2 Tg) were separated into Control (vehicle) and SID (streptozotocin induced diabetes, 200 mg/kg body weight, i.p.). Seven days post‐injection, Wt diabetic animals showed a decrease in PI3K activity and P‐Akt levels, an increase of P‐JNK, P‐p38, pro‐apoptotic Bad and Bax, release of cytochrome c and activities of caspases‐3 and ‐9, leading to an increased apoptotic index. This situation was improved in diabetic COX‐2 Tg. In addition, SID COX‐2 Tg showed increased expression of anti‐apoptotic Mcl‐1 and XIAP. Pro‐apoptotic state in the liver of diabetic animals was improved by over‐expression of COX‐2. We also analyzed the roles of high glucose‐induced apoptosis and hCOX‐2 in vitro. Non‐transfected and hCOX‐2‐transfected cells were cultured at 5 and 25 mM of glucose by 72 h. At 25 mM there was an increase in apoptosis in non‐transfected cells versus those exposed to 5 mM. This increase was partly prevented in transfected cells at 25 mM. Moreover, the protective effect observed in hCOX‐2‐transfected cells was suppressed by addition of DFU (COX‐2 selective inhibitor), and mimicked by addition of PGE2 in non‐transfected cells. Taken together, these results demonstrate that hyperglycemia‐induced hepatic apoptosis is protected by hCOX‐2 expression. J. Cell. Biochem. 114: 669–680, 2013. © 2012 Wiley Periodicals, Inc.